A STRATEGI GURU DALAM MENERAPKAN KEDISIPLINAN PADA KELAS VA SD NEGERI GAYAMSARI 02 - Rositania, Lenisa Wahyu; Damayani, Aries Tika; Mudzanatun, Mudzanatun; Isnuryantono, Effendi (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
This study aims to determine the teacher's strategy in applying discipline through class agreements in the VA class of SD Negeri Gayamsari 02 Semarang. Researchers use a type of descriptive qualitative research. Sources of data were taken from students and teachers of SD Negeri Gayamsari 02. Data collection techniques used interviews, observation and documentation. Meanwhile, the data analysis techniques in this study were data reduction, data processing and drawing conclusions. The results of this study are (a) the teacher applies discipline through habituation activities. (b) the teacher applies discipline through example. (c) the teacher applies discipline through class agreements.